Home versus outpatient pulmonary rehabilitation in COPD: a propensity-matched cohort study. Issue 10 (5th July 2019) - Nolan, Claire Marie; Kaliaraju, Djeya; Jones, Sarah Elizabeth; Patel, Suhani; Barker, Ruth; Walsh, Jessica A; Wynne, Stephanie; Man, William
Abstract : Home-based exercise has been proposed as an equivalent treatment strategy to supervised outpatient pulmonary rehabilitation (PR), but it is not known whether its implementation into clinical practice produces similar benefits to those observed in trials. We compared the real-world responses of 154 patients with COPD undergoing home-based exercise with a matched group attending supervised PR. We observed smaller improvements in exercise capacity with home-based exercise compared with PR, but similar improvements in quality of life. We propose that supervised PR remains the standard of care, with home-based exercise a less effective alternative for those unable to attend PR.